Gambaran Gaya Hidup dan Hipertensi Pada Lansia : A Systematic Review - Rizky Hafifatul Umam; Vivin Nur Hafifah (Jurnal Sains dan Kesehatan, 2021)
The increasing age, the more the risk of increasing blood pressure, especially systolic blood pressure, while diastolic increases only until the age of 55 years. Objective: This systematic review aims to provide an overview of lifestyle and hypertension in the elderly. Methods: This literature-based systematic review was obtained from NCBI, Science Direct, Google Scholar, DOAJ, and a total of 15 articles were reviewed to provide an overview of lifestyle and hypertension in the elderly. Results: Overall, the study results showed a significant reduction in lifestyle-induced blood pressure. There is no predictable pattern of these changes because blood pressure results vary across lifestyle interventions. These findings also reveal that lifestyle modifications lead to lower blood pressure. Conclusion: Therefore, we conclude that lifestyle modification is effective in reducing systolic and diastolic blood pressure in the elderly. Keywords: Lifestyle, Hypertension, Elderly